If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + x = 235 Solving 67 + x = 235 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-67' to each side of the equation. 67 + -67 + x = 235 + -67 Combine like terms: 67 + -67 = 0 0 + x = 235 + -67 x = 235 + -67 Combine like terms: 235 + -67 = 168 x = 168 Simplifying x = 168
| 2s^2+11s+9=-5 | | 29-8p=-7(-8p+5) | | -39+3B=6(-4B+7) | | 2m+40=-7(-8m+2) | | 8a+5b=2000 | | -7n+7(4-8n)=28-2n | | -8(2-2x)-4x=-28+8x | | w^2-14w+x=0 | | 11=1-3r-2r | | 10y+7y-2y=45 | | 8x+7-6=3x | | 3=4r-5r | | 8x+12=2x+168 | | 5y+3w= | | -8y+25=71 | | 6x+14y=148 | | 7k-5k+14=24 | | 8y-3y-15=53.80 | | 377=2*3.15*r*12 | | 77=2*3.15*r*12 | | 10t^2+53t+250=0 | | 2x-3=5+6x | | 4x+5=64 | | 2x^2+4x-3k=0 | | x^2-x^3=0 | | 2x^2+48=16 | | 3x-(7-2x)=5(x-1)-2 | | x-(4.9)=-2.9 | | x[2]=5 | | 93-7x=20x+15 | | x[2]=4 | | 182=7(x+y) |